PENERAPAN PRINSIP MATEMATIKA DALAM IURAN SANTRI DI PESANTREN SUBULUSSALAM TULUNGAGUNG JAWA TIMUR - Ni'ami, Nadia Nur Izza; Nafis, Salsabila Khoirun; Setyawan , Bagus Wahyu (Jurnal Edumatic: Jurnal Pendidikan Matematika, 2023)
The purpose of this research is to collect information about the design, preparation, allocation and accountability of education funding at the Subulussalam 2 Tulungagung Islamic Boarding School and regarding information about the factors that influence educational financing at the Subulussalam 2 Tulungagung Islamic Boarding School mathematically. As well as the benefits of education financing management on the quality of education at the Subulussalam 2 Tulungagung Islamic Boarding School. The data was obtained through interviews with one of the pesantren administrators in the finance section or the treasurer. Data analysis in this study is a quantitative method, which in this study is interpreted as part of a series of systematic investigations of phenomena by collecting existing data to then measure with mathematical statistical techniques how to manage education financing at Pondok Subulussalam 2 Tulungagung. The results of this study generally show that education financing management at the Subulussalam 2 Tulungagung Islamic Boarding School Educational Institution has applied the principles of mathematics.